Recent Trends of Sunscreen Cosmetics Innovative Approaches in Sunscreen Development: Beyond UV Protection - Monisha J, Monisha J; Das, Rahul; Ragul C, Ragul C; Ramprasad B, Ramprasad B (Journal of Neonatal Surgery, 2025)
While the sun is essential for vitamin D synthesis and overall health, it carries a great risk to skin if not managed properly. Ultraviolet radiation (UV), especially its UVA and UVB components, causes sunburns, premature aging and an extra probability of skin cancer. Conventional sunscreens, many exercised but in blocking UV rays, often rely on chemical filters that can raise issues over potential skin irritation, endocrine pathology and environmental burden. This research explores the development and efficacy of a novel Herbal Sunscreen Emulgel formulated with natural ingredients for broad-spectrum sun protection. The emulgel leverages the inherent sun-protective properties of various botanical extracts, offering a safe and eco-friendly alternative to traditional sunscreens. The current study looks into the composition and performance of an innovative Herbal Sunscreen made emulgel with natural components for a wider spectrum of solar coverage. Formulations incorporate the natural solar protective characteristics of different distinctive herbal extract, making them a healthy and natural sun-blocking alternative to conventional sunscreens and showcasing the globe of herbs.